Potensi Konflik Berpengaru Terhadap Peningkatan Ekonomi Masyarakat Kota Gorontalo - Achank, Hasanuddin Bagu; Wekke, Ismail Suwardi; Machmud, Mulyana; Sainuddin, Ibnu Hajar (Jurnal Noken: Ilmu-Ilmu Sosial, 2021)
The method used is a participatory multidimensional approach with the research location of Gorontalo City. This research uses literature study by searching through print media and internet links. The primary data in this study was through interviews with traditional and cultural leaders, religious leaders as well as secondary data from local government agencies and other related institutions (Polri, NGO, CSO, Media). Types of data and sources of conflict include three-year data (2010 – 2012). This research shows that in 2010 the type of conflict between community members and the government was very dominant with the percentage reaching 50%, the next is the potential for natural resource/economic conflict with a percentage of 26%, the potential for communal conflict at 18%, while for the potential for political conflict, Sara and relations industry, only 2% each. In 2011 the type of communal conflict reached 57%, then the potential for political conflict was 22%, the potential for conflict between residents and the apparatus was 10% and the rest the potential for Sara conflict and natural resource/economic conflict were 6% and 5%, respectively. The potential for conflict affects the potential for improving the community's economy and also has an impact on social conflict, so a regional autonomy policy is needed to prevent potential conflicts by optimizing economic achievements and their implementation.